Predictive analytics supporting labor market success - Christopher J. O'Leary; Salomon Orellana; Kevin Doyle; Randall W. Eberts; Ben Damerow; Amy Meyers; Kenneth J. Kline; Anna Wilcoxson; Beth C. Truesdale; Scott Powell (W.E. Upjohn Institute for Employment Research, 2023)
Career Explorer provides customized career exploration tools for workforce development staff and job seekers in Michigan. There are separate Career Explorer modules for mediated staff services and self-service by job seekers. The system was developed by the Michigan Center for Data and Analytics in collaboration with the W.E. Upjohn Institute for Employment Research and Michigan Works! Southwest. It was funded by the U.S. Department of Labor's Office of Workforce Investment and the Schmidt Futures foundation's Data for the American Dream (D4AD) project. In this paper, we describe specifications of the models behind the frontline-staff-mediated version of Career Explorer, which are based on program administrative data, applying data-science methods for predictive analytics. We also describe the self-service Career Explorer, which provides customized labor market information based on published Bureau of Labor Statistics data. Career Explorer became an active feature of Michigan's online reemployment-services system in June 2021.
Keywords: J65; J68; H76; 330; dislocated workers; disadvantaged adults; Workforce Innovation and Opportunity Act (WIOA); labor market information; career exploration; reemployment services; occupational choice; occupational mix of employment; industrial mix of employment; workforce areas